ABOUT ONE APPROACH TO DETERMINING AUDIENCE VOICED IN THE PROCESS OF LEARNING WITH THE HELP OF ERGONOMICS (World Bulletin of Social Sciences, 2022)
In this article, an attempt is made to determine and study the soundness of audiences in the quality management of the learning process in the acquisition of knowledge of students in education using ergonomic models.